[Biology laboratory]
Writing on blackboard reads: 'Bact. 221-02; J. W. Thomas; Office: F.H. 377; Office hours: M 3:10 - 4:30 pm, Th. 11:10 am - 12:00; Quiz and exam schedule for remainder of quarter'.